The systemic angiotensin-II role in the development of retinopathy of prematurity - N. A. Osipova; N. B. Chesnokova; L. A. Katargina; T. A. Pavlenko; O. V. Beznos; A. Yu. Panova (Российский офтальмологический журнал)
Purpose: to determine the role of the systemic angiotensin II (AT-II) in the pathogenesis of retinopathy of prematurity (ROP) and assess its prognostic value.Material and methods. 34 premature infants at risk of developing ROP were examined according to the ophthalmological ROP screening protocol adopted in the Russian Federation. Retrospectively, the infants were divided into 2 groups: those without ROP (n = 15) and those with developed ROP (n = 19). The average gestational age of those without ROP was 28.12 ± 0.64 weeks, their average body weight at birth was 1164 ± 118.6 g. The respective values for the group with ROP were 27.8 ± 0.6 weeks and 1142.6 ± 108.4 g. The two groups had similar extent of general somatic burden. At 32–35 weeks and 36–39 weeks of post-conceptual age (PCA), the infants of both groups were tested for the concentration of AT-II in blood serum using the enzyme-linked immunosorbent assay (ELISA).Results: on the 32–35 week of PCA, the average level of AT-II in blood serum of premature infants of the ROP group was significantly increased as compared to that of the non-ROP group (p = 0.03), while on the 36–39 week of PCA no statistically significant difference between the AT-II levels in the examined groups was found (p = 0.73).Conclusion. We established that the systemic AT-II level has a trigger role in the development of ROP. A high level of this parameter found at the onset of ROP can be considered as an early prognostic criterion for the risk of ROP development.